The Fragile Brain: Understanding Frailty in Neuroanesthesia - Joseph N. Monteiro; Nimisha Thakur; Shwetal Goraksha (Journal of Neuroanaesthesiology and Critical Care)
Frailty is a multidimensional geriatric syndrome characterized by decreased physiological reserve, making patients more vulnerable to stressors, such as surgery and anesthesia. In neuroanesthesia, frailty is particularly relevant due to the high-risk nature of neurosurgical procedures and the potential for significant perioperative stress. Although there are several studies on the implications of frailty in spine surgery, there are lacunae in the knowledge understanding and frailty risk assessment in the cranial cohort of neurosurgical patients. A systemic review process with a qualitative data analysis of the available literature was used to extract data for this review. By identifying, acknowledging, and addressing the knowledge gaps in our understanding of frailty, specifically the cranial cohort, and developing a neuroanesthesia-specific frailty risk index, along with establishing best practice strategy guidelines and institutional protocols, neuroanesthesiologists will enhance and optimize outcomes.